Feasibility study of a photoconductor based dosimeter for quality assurance in radiotherapy. (28th September 2017) - Lee, Y.K.; Kim, S.W.; Kim, J.N.; Kang, Y.N.; Kim, J.Y.; Lee, D.S.; Kim, K.T.; Han, M.J.; Ahn, K.J.; Park, S.K.
Abstract: With the recent market entries of new types of linear accelerators (LINACs) with a multi leaf collimator (MLC) mounted on them, high-precision radiosurgery applying a LINAC to measure high-dose radiation on the target region has been gaining popularity. Systematic and accurate quality assurance (QA) is of vital important for high-precision radiosurgery because of its increased risk of side effects including life-threatening ones such as overexposure of healthy tissues to high-dose radiation beams concentrated on small areas. Therefore, accurate dose and dose-distribution measurements are crucial in the treatment procedure. The accurate measurement of the properties of beams concentrated on small areas requires high-precision dosimeters capable of high-resolution output and dose mapping as well as accurate dosimetry in penumbra regions. In general, the properties of beams concentrated on small areas are measured using thermos luminescent dosimeters (TLD), diode detectors, ion chambers, diamond detectors, or films, and many papers have presented the advantages and disadvantages of each of these detectors for dosimetry. In this study, a solid-state photoconductor dosimeter was developed, and its clinical usability was tested by comparing its relative dosimetric performance with that of a conventional ion chamber. As materials best-suited for radiation dosimeters, four candidates namely lead (II) iodide (PbI 2 ), lead (II) oxide (PbO), mercury (II) iodide (HgI 2 ), and HgI 2 / titanium dioxide (TiO 2 ) composite, the performances of which were proved in previous studies, were used. The electrical properties of each candidate material were examined using the sedimentation method, one of the particle-in-binder (PIB) methods, and unit-cell-type prototypes were fabricated. The unit-cell samples thus prepared were cut into specimens of area 1 × 1 cm 2 with 400- μ  m thickness. The electrical properties of each sample, such as sensitivity, dark current, output current, rising time, falling time, and response delay, were then measured, in addition to the consistency, reproducibility and linearity of each unit-cell. According to the measurement results, HgI 2 /TiO 2 composite outperformed the other candidate materials. A radiation dosimeter with a chamber-type structure was fabricated in this study using a LINAC under accelerating voltages of 6, and 15 MV and compared with a commercial ion chamber. Percent depth dose (PDD) and beam profile were measured on a water phantom at a fixed area of 10 × 10 cm 2  by using the fabricated chamber-type dosimeter, and the values were compared with those measured by a commercial ion chamber. Additionally, a homogeneous phantom was fabricated, and the exposure doses of the center points were measured according to a real treatment plan, followed by a comparison of the measured values as relative values. In this paper, we report that the manufactured dosimeter shows similar characteristics in terms of PDD and beam profile and results for the conventional ion chamber. Based on these results, it is demonstrated that the HgI 2 /TiO 2 -based dosimeter complies with radiotherapy QA requirements, namely Superior detection characteristics, consistency, dose linearity, reproducibility. Thus, we expect the HgI 2 /TiO 2 -based dosimeter to be used commercially in the future.